Justice Education and the Evaluation Process: Crossing Borders - Margaret Martin Barry; Martin Geer; Catherine F. Klein; Ved Kumari (Washington University Journal of Law & Policy, 2008)
This Essay has been written with several purposes: to reflect on our experience and knowledge gained in this workshop; to contribute to the literature on evaluation processes for legal educators; to observe how concepts of justice education and evaluation are defined in a live, cross-cultural dialog; to encourage ourselves and other teachers to place “justice education” as a primary goal in legal education; and to facilitate the holding of similar workshops by others.
Keywords: Clinical legal education; Access to justice; Law students; Performance evaluation; Academic achievement; Career development; Student evaluation; International; Poland; United States